Practices on Al-Awfar and Premium Savings Certificate among Students in UiTM Selangor Puncak Alam Campus / Mohamad Firdaus Rosli - Rosli, Mohamad Firdaus (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This research has discussed people’s practices on Al-Awfar and Premium Savings Certificate among students in UiTM Selangor Puncak Alam Campus. In Malaysia, the Islamic bank institutions need or have to compete with the conventional bank institutions as a confidention to the society. It also aims to convince people about the legality of Al-Awfar and PSC product with Shariah compliance by analyzing its contract. The research methodology will be used in this research are in questionnaire method and library research. The researcher used SSPS and Microsoft Word/Excel as a method to analyse and interpret the data. SSPS is a powerful tool or software that is capable of conducting just about any type of data analysis used in the social sciences, the natural sciences or in the business world. The survey shows the totals of 81 population to the 66 sampling (respondents) from different demographic profiles are selected with some purpose to resolve the doubt of lucky draw-based product and reach the objective of the study.